Aulacoseira giraffensis (Bacillariophyceae), a new diatom species forming massive populations in an Eocene lake - Peter Siver; Alexander Wolfe; Mark Edlund; Joel Sibley; Josh Hausman; Paula Torres; Anne Marie Lott (Plant Ecology and Evolution, 2019)
Background and aims – Diatoms began to inhabit freshwater by at least the Late Cretaceous, becoming well established by the early to middle Eocene. Aulacoseira, an important diatom in numerous ponds, lakes and rivers today, was one of the earliest known genera to colonize freshwater ecosystems. Members of this genus with characteristics familiar to those found on modern species became increasingly more abundant by the Eocene, and continued to thrive throughout the Miocene to the present. We describe a new species of Aulacoseira from an early to middle Eocene site near the Arctic Circle in northern Canada.Methods – Twelve samples taken from the Giraffe Pipe core were analysed in this study. Light and scanning electron microscopy were used to document morphological characters. Morphometric measurements were made from 200 specimens per sample (n = 1200), and used to investigate changes in valve size over time.Key results – The new species, Aulacoseira giraffensis, has valves with a length:width ratio close to 1, a hyaline valve face, straight mantle striae, a shallow ringleiste, branched linking spines, concave-convex complementarity on adjacent valve faces, and rimoportulae with simple papillae-like structure. The suite of characters, especially the highly branched spines, concave-convex valves and simple rimoportulae, is unique for this species. Large numbers of A. giraffensis specimens were found over a ten-metre section of the core, representing thousands of years. These high concentrations are indicative of abundant, bloom-like, growth.Conclusions – The locality represents one of the earliest known records of Aulacoseira dominating a freshwater community. Findings confirm that the morphological body plan for the genus was well established by the Eocene. Although findings indicate evolutionary stasis in morphological structure for A. giraffensis over a time scale of thousands of years, oscillations in valve morphometrics could potentially be used to trace changes in the environment of this ancient Arctic waterbody.